Analisis Laporan Penggunaan Dana Desa Sebagai Pengukur Kinerja Keuangan Pada Kantor Desa Paccerakang Kabupaten Luwu - Johanis Padang; Aminah Aminah; Brisa Makiwan (Journal of Islamic Economics and Finance, 2023)
This study aims to determine the economic level, effectiveness and efficiency of the use of village funds as a measure of financial performance. The subject of this research is Paccerakang Village Office, Luwu Regency. The type of research used in this research is descriptive quantitative. The data processed is the village fund financial report (DDS) report on the village income and expenditure budget from 2021 to 2022. The data collection techniques used are document and library techniques. The data analysis technique used in this research is descriptive comparative analysis with the formula: Economic Ratio, Effectiveness Ratio and Efficiency Ratio. The results showed that the economic performance of the Paccerakang Village Government of Luwu Regency was generally good in managing the finances of the Village Fund (DDS), although the effectiveness performance was less effective in managing the Village Fund (DDS). This can be seen from the results of the calculation of the Economic Ratio, which is categorised as Very Economical because the Economic Average is above 100%, namely 200.31%. While the Effectiveness Ratio is categorised as Less Effective because the average effectiveness is less than 80%, namely 65.6% and the Efficiency Ratio is categorised as Very Efficient because the average efficiency is less than 60%, namely 46.47%.